“Lebanese Protocol”: Ethnic Quota Systems in Kabardino-Balkaria’s Power-Sharing Arrangements (1950s-2020s) - A. A. Tumov; A. A. Tatarov (Научный диалог)
While ethnic quotas remain a cornerstone of power distribution in Kabardino-Balkaria (KBR), their historical evolution and impact on political stability — particularly in the post-Soviet period — remain understudied. This article traces the transformation of ethnic quota systems in KBR from the 1950s through the 2020s, analyzing their role in balancing interests among Kabardin, Balkar, and Russian communities. Drawing on government meeting protocols, electoral commission records, ethnic composition statistics, elite interviews, political memoirs, and parliamentary publications, the study employs mixed-methods analysis. Qualitative and quantitative examination of top officials' ethnic backgrounds reveals: Cases of “rotating” ethnic quotas, informal rules governing long-term ethnic monopolies on specific positions or instances of proportional distribution across groups. The findings demonstrate that ethnic quotas persist as a stabilization mechanism despite tensions with formal legal-state principles. Future research should examine municipal-level implementation and the influence of socioeconomic factors on decision-making processes.